Perancangan Sistem Informasi Project Management Dengan Metode Rapid Aplication Development Berbasis Web (Studi Kasus : Kelaspejwan.Com) - Bagus Budi Pangestu; Niki Ratama (CV. Multi Kreasi Media, 2023)
In carrying out business at KELASPEJWAN.COM, it is still not optimal in controlling and managing project data where KELASPEJWAN.COM currently only uses the help of Microsoft Office applications and Whatsapp to manage project management, which results in the slow process of making reports to see the projects being worked on. The absence of a work scheduling system is also sometimes a problem so that project work does not go well. The purpose of this research is to design a project management information system using the RAD (Rapid Application Development) method. RAD is an incremental software process model that emphasizes a short development cycle. The RAD model is a “high-speed” adaptation of the waterfall model, where rapid development is achieved using a component-based construction approach.Being able to make it easier for companies and employees to monitor work and make reports more efficient then to design and build an application system that is effective in monitoring each project in the company.